Perilaku Konsumen dalam Keputusan Pembelian Wajan Melalui Social Media Facebook di UD Berkat Utama Surabaya - Vedicandro, Clement Timothy (Universitas Widya Kartika Surabaya, 2024)
This company operates in the field of selling frying pans in Indonesia. Specifically, it operates in the distribution of frying pans made from aluminum. Currently, this company uses social media platforms which include social media which is currently popular, where social media has features and makes it easier for people all over Indonesia, even all of Indonesia can reach. This research aims to determine the influence of consumer behavior on the decision to purchase frying pans at UD. Berkat Utama Surabaya, through the social media platform Facebook, understands the influence of Facebook users on the decision to purchase frying pans at UD. Berkat Utama Surabaya and assesses the level of consumer satisfaction after purchasing a frying pan at UD. Berkat Utama Surabaya via social media Facebook. The research method used is qualitative. The respondents in this research were 10 frying pan buyers who made purchases via the Facebook Social Media application. The research variables consist of independent variables: consumer behavior, usage, dependent variable: purchasing decisions. The data analysis technique uses analytical descriptive analysis techniques. The research results show that consumer behavior has an important role in the decision to purchase frying pans via social media Facebook at UD Berkat Utama Surbaya. Various influencing factors such as motivation, perception, learning and consumer attitudes have an impact on purchasing decisions. The use of social media Facebook is effective as a marketing channel and influences frying pan purchasing decisions at UD Berkat Utama Surabaya.